2013
DOI: 10.1016/j.cub.2013.10.068
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic ingestion decreases energy reserves in marine worms

Abstract: The indiscriminate disposal of plastic to the environment is of concern. Microscopic plastic litter (<5 mm diameter; 'microplastic') is increasing in abundance in the marine environment, originating from the fragmentation of plastic items and from industry and personal-care products [1]. On highly impacted beaches, microplastic concentrations (<1mm) can reach 3% by weight, presenting a global conservation issue [2]. Microplastics are a novel substrate for the adherence of hydrophobic contaminants [1], depositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
431
2
16

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 918 publications
(462 citation statements)
references
References 10 publications
13
431
2
16
Order By: Relevance
“…The impacts of plastic ingestion in laboratory studies include gut blockage and physical injury, oxidative stress, altered feeding behavior (7,8), and reduced energy allocation (9), with knock-on effects for growth and reproduction (5). Transfer to tissues of plastics associated with chemicals, many of which possess endocrinedisrupting activity (10), adds to the potential toxicity of ingested particles through activation of signal transduction pathways relevant to hormone action.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The impacts of plastic ingestion in laboratory studies include gut blockage and physical injury, oxidative stress, altered feeding behavior (7,8), and reduced energy allocation (9), with knock-on effects for growth and reproduction (5). Transfer to tissues of plastics associated with chemicals, many of which possess endocrinedisrupting activity (10), adds to the potential toxicity of ingested particles through activation of signal transduction pathways relevant to hormone action.…”
mentioning
confidence: 99%
“…Sediment-dwelling worms exposed to sediments contaminated with PVC microparticles had increased gut transit times and reduced lipid accumulation (8). Similarly, planktonic copepods exposed to micropolystyrene for prolonged periods had reduced food consumption, resulting in reduced reproductive output (9).…”
mentioning
confidence: 99%
“…In a complementary study from Thompson's laboratory, lugworms raised in sediment containing 5% polyvinyl chloride ate less, showed increased inflammation, and also suffered a 50% drop in energy reserves, as measured by levels of carbohydrates, proteins, and fats in their bodies (18). And ongoing work from Rochman's laboratory found that when a fish called the Japanese medaka (Oryzias latipes) was fed environmentally relevant levels of polyethylene marine debris, it experienced liver stress and signs of endocrine disruption (19).…”
Section: Sounding the Alarmmentioning
confidence: 99%
“…Furthermore, it has also been found impacts on oyster reproduction after microplastic exposure (Sussarellu et al, 2015). For lugworm, several studies have found effects on their feeding activity after microplastic exposure; exposure to polyvinylchloride (PVC) (Wright et al, 2013) or polystyrene ) that reduced their feeding activity (number of casts produced). This reduction in feeding activity was also found in another laboratory test looking at the biodegradable polylactic acid (PLA) as well as HDPE and PVC.…”
Section: Effects Of Ingestion On Fish and Invertebrates From Laboratomentioning
confidence: 99%
“…Welden & Cowie 2016 Wright et al 2013 Note: * Intended to be used as an example species -Needs to be carefully considered with further research. ** As far as we know.…”
Section: Biomarker Selectionmentioning
confidence: 99%